2002
DOI: 10.1002/cyto.10172
|View full text |Cite
|
Sign up to set email alerts
|

Static magnetic fields affect calcium fluxes and inhibit stress‐induced apoptosis in human glioblastoma cells

Abstract: Background: Epidemiologic data revealed increased brain tumor incidence in workers exposed to magnetic fields (MFs), raising concerns about the possible link between MF exposure and cancer. However, MFs seem to be neither mutagenic nor tumorigenic. The mechanism of their tumorigenic effect has not been elucidated. Methods: To evaluate the interference of MFs with physical (heat shock, HS) and chemical (etoposide, VP16) induced apoptoses, respectively, we exposed a human glioblastoma primary culture to 6 mT sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 28 publications
4
58
1
2
Order By: Relevance
“…In this regard different models have been proposed. We have recently demonstrated that SMF increase the influx of capacitative calcium in the same cell system that we have used in this research (19). Other investigators have also found an increase of calcium fluxes in other cellular systems (30,31).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In this regard different models have been proposed. We have recently demonstrated that SMF increase the influx of capacitative calcium in the same cell system that we have used in this research (19). Other investigators have also found an increase of calcium fluxes in other cellular systems (30,31).…”
Section: Discussionsupporting
confidence: 63%
“…For the experimental procedures, the cells were plated on glass coverslips and, at a near sub-confluence stage, were exposed to different doses of SMF. We have chosen to investigate glioblastoma cells, as nerve cells have been demonstrated to be one of the preferred targets of magnetic fields (19).…”
Section: Materials and Methods Cell Culturesmentioning
confidence: 99%
“…Both induced and spontaneous apoptosis have been reported to be influenced by SMF exposure. However, some reports have failed to detect any apoptotic effect for SMFs (Teodori et al 2002a(Teodori et al , 2002b(Teodori et al , 2006.…”
Section: Resultsmentioning
confidence: 98%
“…But there is a supposition that the most sensitive element to the magnetic field action a cell plasmolemma due to its bioelectric properties [18,19]. It has been reported previously that SMF of medium intensity can change plasmolemma functions in different types of cells [20][21][22][23][24][25].…”
Section: Magnetic Field Influence On Cells Adhesion Morphology and Pmentioning
confidence: 99%